(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: CXC chemokine receptor-2 (CXCR2) has emerged as a candidate cancer stem-cell related biomarker in breast carcinoma, with reported roles in epithelial–mesenchymal transition, angiogenesis, metastasis and chemoresistance. However, clinicopathological data on CXCR2 expression in routine breast carcinoma specimens remain limited. The present study evaluated CXCR2 immunohistochemical expression in breast carcinoma and assessed its association with estrogen receptor (ER), progesterone receptor (PR), HER2/neu status and clinicopathological parameters. Methods: This cross-sectional analytical study was carried out in the Department of Pathology, Era’s Lucknow Medical College and Hospital, Lucknow, India, over 20 months (April 2020 to November 2021). Fifty newly diagnosed, histopathologically confirmed cases of breast carcinoma were included. Formalin-fixed paraffin-embedded sections were stained with hematoxylin and eosin for diagnosis and grading. Immunohistochemistry was performed for ER, PR, HER2/neu and CXCR2. ER and PR were interpreted as positive or negative; HER2/neu was interpreted according to standard immunohistochemical criteria; CXCR2 immunoreactivity was categorized as low expression (score <6) or high expression (score ≥6). Associations with age, AJCC clinical stage and Nottingham histological grade were analyzed using chi-square testing. Results: Of the 50 patients, 24 (48.0%) were aged <45 years and 26 (52.0%) were aged ≥45 years. Clinical stage II was the most common stage (32/50, 64.0%), and Nottingham grade II was the predominant histological grade (23/50, 46.0%). ER positivity, PR positivity and HER2/neu positivity were observed in 17 (34.0%), 12 (24.0%) and 13 (26.0%) cases, respectively. High CXCR2 expression was identified in 29 (58.0%) cases, while 21 (42.0%) showed low expression. High CXCR2 expression was significantly associated with age ≥45 years (76.9% vs 37.5% in patients <45 years; χ²=7.9, p=0.004) and higher Nottingham grade (grade I: 12.5%, grade II: 73.9%, grade III: 81.8%; χ²=18.25, p=0.0001). CXCR2 expression increased with advancing clinical stage, but the association was not statistically significant (χ²=3.2, p=0.19). HER2/neu expression showed a significant association with clinical stage (χ²=10.7, p=0.01), whereas ER and PR did not show significant associations with age, stage or grade. Conclusions: CXCR2 is frequently expressed in breast carcinoma and demonstrates significant association with older age and higher histological grade. These findings support a potential role for CXCR2 as a biomarker of tumor aggressiveness and a candidate prognostic stem-cell related marker in breast carcinoma. Larger multicentric studies with survival analysis and molecular validation are required to confirm its clinical utility.